Conductive silver paste and preparation method and application thereof

By using co-sintered glass powder and ceramic powder, the problem of conductive silver paste being cured in the high-temperature curing process is solved, and the photoelectric conversion efficiency and welding tension of solar cells are improved.

CN119763891AActive Publication Date: 2025-04-04TUNGHSU TECH GRP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411746043.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-04
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

During the high-temperature curing process, the conductive silver paste used for the front of existing solar cells has problems such that Ag and glass powder are cured as the same as that of glass powder, and the silver powder floats or sinks, which affects the photoelectric conversion efficiency.

Method used

Co-sintered glass powder and ceramic powder are used to mix the glass powder and ceramic powder and sinter it to prepare a composite material and silver powder, which significantly improves the bonding performance of conductive silver paste.

Benefits of technology

The density and adhesion of conductive silver paste are improved, the problem of high-temperature curing of silver powder and glass powder is overcome, and the photoelectric conversion efficiency and welding tension are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to conductive silver paste and a preparation method and application thereof, the conductive silver paste comprises silver powder, a composite material and an organic carrier, and the composite material is a co-sintered product of glass powder and ceramic powder. The conductive silver paste disclosed by the invention has relatively low resistivity, relatively high welding tension and cold and hot impact resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the photovoltaic field, and in particular to a conductive silver paste and a preparation method and application thereof. Background Art

[0002] Conductive silver paste (front silver paste) used on the front of solar cells plays a vital role in the manufacture of solar cells. Front silver paste is mainly used to make the conductive path on the front of the solar cell, especially in the silicon solar cell, it connects the metal grid between the cells to form the current guide and distribution. The conductive silver paste used on the front of the solar cell mainly plays the role of making the conductive path and improving the photoelectric conversion efficiency. At the same time, it should also have good weather resistance and oxidation resistance. The front silver paste forms a fine conductive path on the front of the solar cell, that is, the grid line, which is responsible for collecting and transmitting the current generated by the photovoltaic effect. The conductive performance directly affects the series resistance of the solar cell, and then affects the photoelectric conversion efficiency of the cell. In outdoor environments, solar cells need to withstand the test of various climatic conditions. The front silver paste needs to have good weather resistance and oxidation resistance to ensure the stability and reliability of the battery during long-term use.

[0003] The existing conductive silver paste for the front side of solar cells is mainly composed of silver powder, glass powder, organic carrier and other components. After long-term application, it is found that during the screen printing and sintering processes, the existing conductive silver paste for the front side of solar cells has problems such as asynchronous high-temperature curing of Ag and glass powder, rapid curing of silver powder, and floating or sinking of silver powder, which in turn affects the photoelectric conversion efficiency. In addition, the type and content of glass powder have an important influence on the electrical properties and adhesion of silver paste.

[0004] Therefore, the conductive silver paste used on the front of solar cells is one of the indispensable key materials in the manufacture of solar cells. With the continuous development of solar cell technology and the continuous expansion of application fields, the adhesion and conductive properties of the front silver paste will also be continuously optimized and improved. Summary of the invention

[0005] In view of the defects existing in the prior art, the object of the present invention is to provide a conductive silver paste and a preparation method thereof. The conductive silver paste of the present invention can improve electrical properties, has lower resistivity, higher welding tension and resistance to cold and hot shocks.

[0006] To achieve the above objectives, the first aspect of the present invention provides a conductive silver paste, comprising silver powder, a composite material and an organic carrier, wherein the composite material is a co-sintered product of glass powder and ceramic powder.

[0007] On the basis of the above technical solution, the weight ratio of glass powder to ceramic powder is 1:0.1-0.4. Preferably, the weight ratio of glass powder to ceramic powder is 1:0.2-0.3. For example but not limited to 1:0.2, 1:0.21, 1:0.22, 1:0.23, 1:0.24, 1:0.25, 1:0.26, 1:0.27, 1:0.28, 1:0.29, 1:0.3, etc.

[0008] On the basis of the above technical solution, the preparation method of the co-sintered product comprises: mixing glass powder and ceramic powder and sintering. In the present invention, after co-sintering, compounding with silver powder and the like can significantly improve the bonding performance of the conductive silver paste and improve the mismatch problem between the silver powder and the glass bonding phase.

[0009] On the basis of the above technical solution, the sintering conditions include: a temperature of 700-850°C and a time of 2-4h. In the present invention, the sintering temperature may be, but not limited to, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, etc. The sintering time may be, but not limited to, 2h, 2.5h, 3h, 3.5h, 4h, etc.

[0010] On the basis of the above technical solution, the glass powder contains SiO 2 and PbO, and SiO 2 The weight ratio of SiO to PbO is 1:0.6-0.8. 2 With PbO in the range of 1:0.6-0.8, the electrical properties are better.

[0011] On the basis of the above technical solution, the glass powder further contains Al 2 O 3 、Na 2 O.K 2 O, MgO, CaO, MoO 2 and SnO 2 One or more of .

[0012] On the basis of the above technical solution, preferably, based on the total weight of the glass powder, SiO 2 The content of PbO is 25-40% by weight, and the content of Al is 30-60% by weight. 2 O 3 The content of Na is 0.1-3% by weight 2 The content of O is 5-20% by weight, K 2 The content of O is 0.1-1 wt%, the content of MgO is 1-6 wt%, the content of CaO is 6-12 wt%, and the content of MoO2 The content is 0-1% by weight, SnO 2 The content is 0-1% by weight.

[0013] Based on the above technical solution, the ceramic powder contains fused quartz and zirconium oxide.

[0014] On the basis of the above technical solution, the weight ratio of fused silica to zirconium oxide in the ceramic powder is 1:1-2. In the present invention, the weight ratio of fused silica to zirconium oxide can be but not limited to 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, etc.

[0015] On the basis of the above technical solution, based on the total weight of the conductive silver paste, the content of silver powder is 80-95 weight %, the content of the composite material is 1-5 weight %, and the content of the organic carrier is 4-15 weight %.

[0016] On the basis of the above technical solution, the organic carrier includes a solvent and optional additives.

[0017] On the basis of the above technical solution, the solvent is selected from one or more of diethylene glycol butyl ether acetate, dimethyl glutarate, dimethyl succinate and dimethyl adipate.

[0018] On the basis of the above technical solution, the additive is selected from one or more of a dispersant, a leveling agent, a thixotropic agent, a coupling agent and a defoaming agent. In the present invention, the dispersant, the leveling agent, the thixotropic agent, the coupling agent and the defoaming agent can be conventional options in the art, for example, the dispersant can be BYK-W980, etc.; the coupling agent can be a silane coupling agent, etc.; the leveling agent can be castor oil, etc.; the defoaming agent can be dimethyl silicone oil, etc. In the present invention, the additive can be added in an amount of 0.1-0.5 parts by weight based on the total weight of the conductive silver paste. For example, but not limited to 0.1 parts by weight, 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight, 0.5 parts by weight, etc.

[0019] On the basis of the above technical solution, the conductive silver paste is a conductive silver paste for the front side of the solar cell. The front side silver paste mainly collects and conducts photogenerated carriers, and the back side silver paste mainly has a bonding effect (lower conductivity requirements), so the front side silver paste is the main one. The conductive silver paste of the present invention is more suitable as the front side of the solar cell.

[0020] The second aspect of the present invention provides a method for preparing the conductive silver paste, comprising: mixing silver powder, composite material and organic carrier. The mixing may be, but is not limited to, rolling in a three-roll mill to uniformly disperse.

[0021] The third aspect of the present invention provides the application of the conductive silver paste in the photovoltaic field, especially as a conductive silver paste for the front side of a solar cell.

[0022] Beneficial effects of the present invention:

[0023] (1) The present invention uses co-sintered glass powder and ceramic powder, which can improve the problem of poor bonding due to the large difference in expansion coefficient between glass powder and silver powder. The lead-containing glass powder is used in combination with fused quartz and zirconia ceramics to improve the compactness of the conductive silver paste. When printing, the conductive silver paste formula of the present invention can overcome the problems of asynchronous high-temperature curing of silver powder and glass powder, rapid curing of silver powder, and floating or sinking of silver powder, thereby improving the photoelectric conversion efficiency. In addition, the co-sintered glass powder and ceramic powder can improve the adhesion, and the prepared silver line width is narrower, with better effect.

[0024] (2) In the present invention, the addition of PbO can promote the solidification of silver powder, improve the wettability of silver powder, and further improve the electrical properties and adhesion. DETAILED DESCRIPTION

[0025] In the following technical description, for the convenience of explanation, a plurality of details are provided to provide a full understanding of the disclosed embodiments. However, one or more embodiments can still be implemented without these details. In other cases, well-known structures and devices can be simplified for display.

[0026] The terms "first", "second", etc. in the description and claims of the disclosed embodiments are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchanged where appropriate, so that the embodiments of the disclosed embodiments described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.

[0027] The following are examples. In the following examples and comparative examples, all the raw materials used were obtained from commercial sources.

[0028] Example 1

[0029] Step 1: Prepare glass powder:

[0030] 45 wt% SiO 2 , 31.5 wt% PbO, 1 wt% Al 2 O 3 , 10 wt% Na 2 O, 0.5 wt% K 2 O, 3 wt% MgO, 8 wt% CaO, 0.5 wt% MoO 2 , 0.5 wt% SnO 2The mixture is mixed to obtain glass powder.

[0031] Step 2: Preparation of ceramic powder:

[0032] 40 wt% of fused silica and 60 wt% of zirconium oxide are mixed to obtain ceramic powder.

[0033] Step 3: Prepare a co-sintered product of glass powder and ceramic powder

[0034] The glass powder obtained in step 1 and the ceramic powder obtained in step 2 are mixed in a weight ratio of 1:0.2, sintered at 750° C. for 2 h, and ground into particles after cooling to obtain a composite material.

[0035] Step 4: Prepare conductive silver paste:

[0036] 90 wt % of silver powder, 3 wt % of the composite material, 6.6 wt % of diethylene glycol butyl ether acetate (organic carrier), 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980 were mixed, and ultrasonic dispersion and three-roll mill mixing were used to evenly disperse the slurry to obtain a conductive silver paste.

[0037] Example 2

[0038] Step 1: Prepare glass powder:

[0039] 32 wt% SiO 2 , 26 wt% PbO, 3 wt% Al 2 O 3 , 20 wt% Na 2 O, 0.1 wt% K 2 O, 6 wt% MgO, 11 wt% CaO, 0.9 wt% MoO 2 , 1 wt% SnO 2 The mixture is mixed to obtain glass powder.

[0040] Step 2: Preparation of ceramic powder:

[0041] 35 wt% of fused silica and 65 wt% of zirconium oxide are mixed to obtain ceramic powder.

[0042] Step 3: Prepare a co-sintered product of glass powder and ceramic powder

[0043] The glass powder obtained in step 1 and the ceramic powder obtained in step 2 are mixed in a weight ratio of 1:0.2, sintered at 800° C. for 3 hours, and ground into particles after cooling to obtain a composite material.

[0044] Step 4: Prepare conductive silver paste:

[0045] 90 wt % of silver powder, 3 wt % of the composite material, 6.6 wt % of diethylene glycol butyl ether acetate (organic carrier), 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980 were mixed, and ultrasonic dispersion and three-roll mill mixing were used to evenly disperse the slurry to obtain a conductive silver paste.

[0046] Example 3

[0047] Step 1: Prepare glass powder:

[0048] 45 wt% SiO 2 , 31.5 wt% PbO, 1 wt% Al 2 O 3 , 10 wt% Na 2 O, 0.5 wt% K 2 O, 3 wt% MgO, 8 wt% CaO, 0.5 wt% MoO 2 , 0.5 wt% SnO 2 The mixture is mixed to obtain glass powder.

[0049] Step 2: Preparation of ceramic powder:

[0050] 50 wt% of fused silica and 50 wt% of zirconium oxide are mixed to obtain ceramic powder.

[0051] Step 3: Prepare a co-sintered product of glass powder and ceramic powder

[0052] The glass powder obtained in step 1 and the ceramic powder obtained in step 2 are mixed in a weight ratio of 1:0.2, sintered at 750° C. for 2 h, and ground into particles after cooling to obtain a composite material.

[0053] Step 4: Prepare conductive silver paste:

[0054] 90 wt % of silver powder, 3 wt % of the composite material, 6.6 wt % of diethylene glycol butyl ether acetate (organic carrier), 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980 were mixed, and ultrasonic dispersion and three-roll mill mixing were used to evenly disperse the slurry to obtain a conductive silver paste.

[0055] Example 4

[0056] Step 1: Prepare glass powder:

[0057] 45 wt% SiO 2 , 31.5 wt% PbO, 1 wt% Al 2 O 3 , 10 wt% Na 2 O, 0.5 wt% K 2O, 3 wt% MgO, 8 wt% CaO, 0.5 wt% MoO 2 , 0.5 wt% SnO 2 The mixture is mixed to obtain glass powder.

[0058] Step 2: Preparation of ceramic powder:

[0059] 40 wt% of fused silica and 60 wt% of zirconium oxide are mixed to obtain ceramic powder.

[0060] Step 3: Prepare a co-sintered product of glass powder and ceramic powder

[0061] The glass powder obtained in step 1 and the ceramic powder obtained in step 2 are mixed in a weight ratio of 1:0.3, sintered at 750° C. for 2 h, and ground into particles after cooling to obtain a composite material.

[0062] Step 4: Prepare conductive silver paste:

[0063] 90 wt % of silver powder, 3 wt % of the composite material, 6.6 wt % of diethylene glycol butyl ether acetate (organic carrier), 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980 were mixed, and ultrasonic dispersion and three-roll mill mixing were used to evenly disperse the slurry to obtain a conductive silver paste.

[0064] Example 5

[0065] Step 1: Prepare glass powder:

[0066] 45 wt% SiO 2 , 31.5 wt% PbO, 1 wt% Al 2 O 3 , 10 wt% Na 2 O, 0.5 wt% K 2 O, 3 wt% MgO, 8 wt% CaO, 0.5 wt% MoO 2 , 0.5 wt% SnO 2 The mixture is mixed to obtain glass powder.

[0067] Step 2: Preparation of ceramic powder:

[0068] 40 wt% of fused silica and 60 wt% of zirconium oxide are mixed to obtain ceramic powder.

[0069] Step 3: Prepare a co-sintered product of glass powder and ceramic powder

[0070] The glass powder obtained in step 1 and the ceramic powder obtained in step 2 are mixed in a weight ratio of 1:0.2, sintered at 750° C. for 2 h, and ground into particles after cooling to obtain a composite material.

[0071] Step 4: Prepare conductive silver paste:

[0072] 90 wt % of silver powder, 5 wt % of the composite material, 4.6 wt % of diethylene glycol butyl ether acetate (organic carrier), 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980 were mixed, and ultrasonic dispersion and three-roll mill mixing were used to evenly disperse the slurry to obtain a conductive silver paste.

[0073] Example 6

[0074] Step 1: Prepare glass powder:

[0075] 45 wt% SiO 2 , 31.5 wt% PbO, 1 wt% Al 2 O 3 , 10 wt% Na 2 O, 0.5 wt% K 2 O, 3 wt% MgO, 8 wt% CaO, 0.5 wt% MoO 2 , 0.5 wt% SnO 2 The mixture is mixed to obtain glass powder.

[0076] Step 2: Preparation of ceramic powder:

[0077] 40 wt% of fused silica and 60 wt% of zirconium oxide are mixed to obtain ceramic powder.

[0078] Step 3: Prepare a co-sintered product of glass powder and ceramic powder

[0079] The glass powder obtained in step 1 and the ceramic powder obtained in step 2 are mixed in a weight ratio of 1:0.1, sintered at 750° C. for 2 h, and ground into particles after cooling to obtain a composite material.

[0080] Step 4: Prepare conductive silver paste:

[0081] 90 wt % of silver powder, 3 wt % of the composite material, 6.6 wt % of diethylene glycol butyl ether acetate (organic carrier), 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980 were mixed, and ultrasonic dispersion and three-roll mill mixing were used to evenly disperse the slurry to obtain a conductive silver paste.

[0082] Example 7

[0083] Step 1: Prepare glass powder:

[0084] 45 wt% SiO 2 , 31.5 wt% PbO, 1 wt% Al 2 O 3, 10 wt% Na 2 O, 0.5 wt% K 2 O, 3 wt% MgO, 8 wt% CaO, 0.5 wt% MoO 2 , 0.5 wt% SnO 2 The mixture is mixed to obtain glass powder.

[0085] Step 2: Preparation of ceramic powder:

[0086] 40 wt% of fused silica and 60 wt% of zirconium oxide are mixed to obtain ceramic powder.

[0087] Step 3: Prepare a co-sintered product of glass powder and ceramic powder

[0088] The glass powder obtained in step 1 and the ceramic powder obtained in step 2 are mixed in a weight ratio of 1:0.4, sintered at 750° C. for 2 h, and ground into particles after cooling to obtain a composite material.

[0089] Step 4: Prepare conductive silver paste:

[0090] 90 wt % of silver powder, 3 wt % of the composite material, 6.6 wt % of diethylene glycol butyl ether acetate (organic carrier), 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980 were mixed, and ultrasonic dispersion and three-roll mill mixing were used to evenly disperse the slurry to obtain a conductive silver paste.

[0091] Example 8

[0092] Step 1: Prepare glass powder:

[0093] 45 wt% SiO 2 , 31.5 wt% PbO, 1 wt% Al 2 O 3 , 10 wt% Na 2 O, 0.5 wt% K 2 O, 3 wt% MgO, 8 wt% CaO, 0.5 wt% MoO 2 , 0.5 wt% SnO 2 The mixture is mixed to obtain glass powder.

[0094] Step 2: Preparation of ceramic powder:

[0095] 40 wt% of fused silica and 60 wt% of zirconium oxide are mixed to obtain ceramic powder.

[0096] Step 3: Prepare a co-sintered product of glass powder and ceramic powder

[0097] The glass powder obtained in step 1 and the ceramic powder obtained in step 2 are mixed in a weight ratio of 1:0.8, sintered at 750° C. for 2 h, and ground into particles after cooling to obtain a composite material.

[0098] Step 4: Prepare conductive silver paste:

[0099] 90 wt % of silver powder, 3 wt % of the composite material, 6.6 wt % of diethylene glycol butyl ether acetate (organic carrier), 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980 were mixed, and ultrasonic dispersion and three-roll mill mixing were used to evenly disperse the slurry to obtain a conductive silver paste.

[0100] Example 9

[0101] The method of Example 1 is followed, except that PbO is replaced by SiO in the glass powder. 2 ,Right now:

[0102] Step 1: Prepare glass powder:

[0103] 76.5 wt% SiO 2 , 1 wt% Al 2 O 3 , 10 wt% Na 2 O, 0.5 wt% K 2 O, 3 wt% MgO, 8 wt% CaO, 0.5 wt% MoO 2 , 0.5 wt% SnO 2 The mixture is mixed to obtain glass powder.

[0104] Step 2: Preparation of ceramic powder:

[0105] 40 wt% of fused silica and 60 wt% of zirconium oxide are mixed to obtain ceramic powder.

[0106] Step 3: Prepare a co-sintered product of glass powder and ceramic powder

[0107] The glass powder obtained in step 1 and the ceramic powder obtained in step 2 are mixed in a weight ratio of 1:0.2, sintered at 750° C. for 2 h, and ground into particles after cooling to obtain a composite material.

[0108] Step 4: Prepare conductive silver paste:

[0109] 90 wt % of silver powder, 3 wt % of composite material, 6.6 wt % of diethylene glycol butyl ether acetate (organic carrier), 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980 were mixed, and ultrasonic dispersion and three-roll mill kneading were used to evenly disperse the slurry to obtain a conductive silver paste.

[0110] Comparative Example 1

[0111] The method of Example 1 is followed, except that ceramic powder is not used, that is:

[0112] Step 1: Prepare glass powder:

[0113] 45 wt% SiO 2 , 31.5 wt% PbO, 1 wt% Al 2 O 3 , 10 wt% Na 2 O, 0.5 wt% K 2 O, 3 wt% MgO, 8 wt% CaO, 0.5 wt% MoO 2 , 0.5 wt% SnO 2 The mixture is mixed to obtain glass powder.

[0114] Step 2: Prepare conductive silver paste:

[0115] 90 wt % of silver powder, 3 wt % of glass powder, 6.6 wt % of diethylene glycol butyl ether acetate (organic carrier), 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980 were mixed, and ultrasonic dispersion and three-roll mill mixing were used to evenly disperse the slurry to obtain a conductive silver paste.

[0116] Comparative Example 2

[0117] The method of Example 1 is followed, except that fused silica is replaced with zirconium oxide, that is:

[0118] Step 1: Prepare glass powder:

[0119] 45 wt% SiO 2 , 31.5 wt% PbO, 1 wt% Al 2 O 3 , 10 wt% Na 2 O, 0.5 wt% K 2 O, 3 wt% MgO, 8 wt% CaO, 0.5 wt% MoO 2 , 0.5 wt% SnO 2 The mixture is mixed to obtain glass powder.

[0120] Step 2: Prepare a co-sintered product of glass powder and ceramic powder

[0121] The glass powder obtained in step 1 is mixed with zirconium oxide in a weight ratio of 1:0.2, and sintered at 750° C. for 2 hours. After cooling, the mixture is ground into particles to obtain a composite material.

[0122] Step 3: Prepare conductive silver paste:

[0123] 90 wt % of silver powder, 3 wt % of the composite material, 6.6 wt % of diethylene glycol butyl ether acetate (organic carrier), 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980 were mixed, and ultrasonic dispersion and three-roll mill mixing were used to evenly disperse the slurry to obtain a conductive silver paste.

[0124] Comparative Example 3

[0125] The method of Example 1 is followed, except that zirconium oxide is replaced by:

[0126] Step 1: Prepare glass powder:

[0127] 45 wt% SiO 2 , 31.5 wt% PbO, 1 wt% Al 2 O 3 , 10 wt% Na 2 O, 0.5 wt% K 2 O, 3 wt% MgO, 8 wt% CaO, 0.5 wt% MoO 2 , 0.5 wt% SnO 2 The mixture is mixed to obtain glass powder.

[0128] Step 2: Prepare a co-sintered product of glass powder and ceramic powder

[0129] The glass powder obtained in step 1 and fused quartz are mixed in a weight ratio of 1:0.2, sintered at 750° C. for 2 h, and ground into particles after cooling to obtain a composite material.

[0130] Step 3: Prepare conductive silver paste:

[0131] 90 wt % of silver powder, 3 wt % of the composite material, 6.6 wt % of diethylene glycol butyl ether acetate (organic carrier), 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980 were mixed, and ultrasonic dispersion and three-roll mill mixing were used to evenly disperse the slurry to obtain a conductive silver paste.

[0132] Comparative Example 4

[0133] The method of Example 1 is the same, except that the glass powder and the ceramic powder are not co-sintered, that is:

[0134] Step 1: Prepare glass powder:

[0135] 45 wt% SiO 2 , 31.5 wt% PbO, 1 wt% Al 2 O 3 , 10 wt% Na 2O, 0.5 wt% K 2 O, 3 wt% MgO, 8 wt% CaO, 0.5 wt% MoO 2 , 0.5 wt% SnO 2 The mixture is mixed to obtain glass powder.

[0136] Step 2: Preparation of ceramic powder:

[0137] 40 wt% of fused silica and 60 wt% of zirconium oxide are mixed to obtain ceramic powder.

[0138] Step 3: Prepare a co-sintered product of glass powder and ceramic powder

[0139] The glass powder obtained in step 1 and the ceramic powder obtained in step 2 are mixed at a weight ratio of 1:0.2 to obtain a composite material.

[0140] Step 4: Prepare conductive silver paste:

[0141] 90 wt % of silver powder, 3 wt % of the composite material, 6.6 wt % of diethylene glycol butyl ether acetate (organic carrier), 0.2 wt % of castor oil leveling agent and 0.2 wt % of dispersant BYK-W980 were mixed, and ultrasonic dispersion and three-roll mill mixing were used to evenly disperse the slurry to obtain a conductive silver paste.

[0142] Test Case

[0143] Performance test: The resistivity, contact resistivity, peel strength and aging performance of the electrodes prepared with the conductive silver pastes of the embodiment and the comparative example were tested respectively. The results are shown in Table 1.

[0144] (1) Test method for resistivity: The conductive pastes of the embodiment and the comparative example were screen-printed and coated on an N-type TOPCon solar blue film, respectively, and vacuum dried at room temperature for 3 hours. Then, the film was cured using circulating hot air at 200°C for 30 minutes to obtain a fine-wire electrode. The resistance of the fine-wire electrode was then measured using an AEMC 6240 microresistance meter, and the width and length of the fine wire were measured using a WI-5000 interferometric coaxial three-dimensional stereo microscope. The pattern specifications of the fine-wire electrode formed above are that the width of the middle line segment is 40 μm, the length is 9 cm, and the contact pads at the head and tail are 2 mm × 2 mm. The line resistance is measured by four-terminal sensing between the contact pads, the measured resistance is standardized by the grid line length, and multiplied by the cross-sectional area (measured using an α step profiler) to obtain the resistivity (ρ) of the grid line. Each resistivity data set is obtained by averaging the values ​​measured on four different grid lines.

[0145] (2) Test method for contact resistivity: The conductive pastes of the embodiment and the comparative example were screen-printed and coated on an N-type TOPCon solar blue film, and vacuum dried at room temperature for 3 hours. Then, the film was cured using circulating hot air at 200°C for 50 minutes to obtain a fine-line electrode. The electrode pattern consisted of 5 linear electrodes with a line width of 0.5 mm and a length of 50 mm, with a line spacing of 3 mm. Then, an AEMC 6240 microresistance meter was used to measure the resistance between line electrodes with different spacings, and the distance was calculated using the transmission line model method (TLM) to obtain the contact resistivity (R c ).

[0146] (3) Test method for peel strength: The conductive pastes of the embodiment and the comparative example are screen-printed and coated on the N-type TOPCon solar blue film, and vacuum dried at room temperature for 3 hours. Then, the film is cured using circulating hot air at 200°C for 50 minutes to obtain a fine-wire electrode. To obtain an electrode pattern. The pattern specifications of the test electrode are 5 cm long and 2 mm wide, and then a tinned copper tape with a width of 1 mm is welded to the test electrode. The substrate is fixed on the tensiometer platform to test the peel strength. The tensiometer type is NLB - 100 electronic push-pull pressure gauge. The test conditions are to peel off the solder strip at an angle of 180° at a speed of 60mm / min and obtain the tensile force value, which is recorded every 1 second. The obtained tension is the average value of the 5cm long electrode.

[0147] (4) Test method for aging resistance: Test the attenuation of the photoelectric conversion efficiency after 200 hot and cold cycles. Aging resistance (attenuation %) = (initial photoelectric conversion efficiency - photoelectric conversion efficiency after 200 hot and cold cycles) / initial photoelectric conversion efficiency × 100%.

[0148] Table 1

[0149]

[0150] It can be seen from the above table that the conductive silver paste for solar cells prepared by adopting the formula of the present invention can reduce the resistivity and contact resistance and improve the welding tension and aging resistance performance.

[0151] The present application is not limited to the embodiments described above, and various modifications and changes may be made without departing from the scope thereof. The scope of the present application is limited only by the appended claims.

[0152] In the present application, each embodiment may focus on the differences from other embodiments, and the same or similar parts between the embodiments may refer to each other.

Claims

1. A conductive silver paste comprising silver powder, a composite material and an organic carrier, wherein: The composite material is a co-sintered product of glass powder and ceramic powder.

2. The conductive silver paste according to claim 1, characterized in that: The weight ratio of glass powder to ceramic powder is 1:0.1-0.

4.

3. The conductive silver paste according to claim 1 or 2, characterized in that: The preparation method of the co-sintered product comprises: mixing glass powder and ceramic powder, and sintering. Preferably, the sintering conditions include: a temperature of 700-850° C. and a sintering time of 2-4 hours.

4. The conductive silver paste according to any one of claims 1 to 3, characterized in that: The glass powder contains SiO2 and PbO, and the weight ratio of SiO2 to PbO is 1:0.6-0.8; Preferably, the glass powder further contains one or more of Al2O3, Na2O, K2O, MgO, CaO, MoO2 and SnO2; More preferably, based on the total weight of the glass powder, the content of SiO2 is 30-60 weight%, the content of PbO is 25-40 weight%, the content of Al2O3 is 0.1-3 weight%, the content of Na2O is 5-20 weight%, the content of K2O is 0.1-1 weight%, the content of MgO is 1-6 weight%, the content of CaO is 6-12 weight%, the content of MoO2 is 0-1 weight%, and the content of SnO2 is 0-1 weight%.

5. The conductive silver paste according to any one of claims 1 to 4, characterized in that: The ceramic powder contains fused quartz and zirconium oxide. Preferably, the weight ratio of fused quartz to zirconium oxide in the ceramic powder is 1:1-2.

6. The conductive silver paste according to any one of claims 1 to 5, characterized in that: Based on the total weight of the conductive silver paste, the content of the silver powder is 80-95 weight %, the content of the composite material is 1-5 weight %, and the content of the organic carrier is 4-15 weight %.

7. The conductive silver paste according to any one of claims 1 to 6, characterized in that: The organic vehicle comprises a solvent and optional additives; Preferably, the solvent is selected from one or more of diethylene glycol butyl ether acetate, dimethyl glutarate, dimethyl succinate and dimethyl adipate; Preferably, the additive is selected from one or more of a dispersant, a leveling agent, a thixotropic agent, a coupling agent and a defoaming agent.

8. The conductive silver paste according to any one of claims 1 to 7, characterized in that: The conductive silver paste is a conductive silver paste for the front side of a solar cell.

9. The method for preparing the conductive silver paste according to any one of claims 1 to 8, comprising: The silver powder, the composite material and the organic carrier are mixed.

10. Use of the conductive silver paste according to any one of claims 1 to 8 in the photovoltaic field, especially as conductive silver paste for the front side of solar cells.

Citation Information

Patent Citations

  • Lead-free positive silver paste applied to silicon solar cell and preparation method thereof

    CN106653147A

  • Crystalline silicon solar cell front silver paste and preparation method thereof

    CN108766618A

  • Conductive silver paste for filtering and preparation method thereof

    CN112489850A

  • Photosensitive glass paste, electronic component, and method for producing electronic component

    US20190112222A1

  • Glass ceramic material, laminate, and electronic component

    US20210309562A1